The killers - O'Gorman Hugh; Warner, Kathleen; Dennehy, Ed; Coon, Gene L.; Siegel, Don, 1912-; Marvin, Lee.; Dickinson, Angie; Cassavetes, John, 1929-; Reagan, Ronald; Gulager, Clu.; Hemingway, Ernest, 1899-1961.; Universal-International (Firm); et al. (Cal. Peacock Films, 2003)
Melodramatic thriller based on the Hemingway story about two hit men who become curious about the life and death of the man they were hired to kill.
Based on the short story, The killers, by Ernest Hemingway.
Originally released as motion pictures in 1946 and 1964.
Special edition double-disc set features The killers (1946) and The killers (1964). Includes Andrei Tarkovsky's 1956 student film version of The killers.
1946 version: Burt Lancaster, Ava Gardner ; 1964 version: Lee Marvin, Angie Dickinson, John Cassavettes, Clu Gulager, Ronald Reagan.
DVD; Dolby digital mono.
Keywords: Feature films; Film noir; Detective and mystery films